2023
DOI: 10.34080/os.v32.22615
|View full text |Cite
|
Sign up to set email alerts
|

Diet and prey size preference in Razorbills Alca torda breeding at Stora Karlsö, Sweden

Abstract: The Razorbill Alca torda is one of three auk species breeding in Sweden, often occurring in colonies with Common Guillemot Uria aalge. The largest colony in the Baltic Sea is situated on the island Stora Karlsö west of Gotland. During the chick-rearing phase, Razorbills forage at sea and return to feed the young with single or multiple prey carried sideways in the bill, unlike Common Guillemots that carry a single fish in the middle of the bill. Clupeids, especially sprat Sprattus sprattus, are the main prey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…(e.g., Atlantic Ocean), probably due to differences in dietary habits during winter. However, since Razorbills are known to usually target prey with an average body length of 115 mm (Engvall et al, 2022) and generally smaller than 250 mm (Bradstreet & Brown, 1985), the authors suggested that some fish species of that size, such as Sardina pilchardus, present both in the Atlantic and in the Mediterranean, could constitute potential Razorbill prey in the Mediterranean as well. The Razorbill is a specialized but highly flexible top predator capable of adapting rapidly to climate change and able to track changes of preferred prey even well outside the boundary of their normal range (e.g., Gaston & Woo, 2008), and can shift dietary trophic levels under certain circumstances (e.g., Glew et al, 2019).…”
Section: Statusmentioning
confidence: 99%
“…(e.g., Atlantic Ocean), probably due to differences in dietary habits during winter. However, since Razorbills are known to usually target prey with an average body length of 115 mm (Engvall et al, 2022) and generally smaller than 250 mm (Bradstreet & Brown, 1985), the authors suggested that some fish species of that size, such as Sardina pilchardus, present both in the Atlantic and in the Mediterranean, could constitute potential Razorbill prey in the Mediterranean as well. The Razorbill is a specialized but highly flexible top predator capable of adapting rapidly to climate change and able to track changes of preferred prey even well outside the boundary of their normal range (e.g., Gaston & Woo, 2008), and can shift dietary trophic levels under certain circumstances (e.g., Glew et al, 2019).…”
Section: Statusmentioning
confidence: 99%